Microbiological studies of a new naphthoquinone semicarbazone derivatives - Baghdad Science Journal (مجلة بغداد للعلوم)
The antimicrobial activity of two naphthoquinone semicarbazone derivatives (Two newly synthesized compounds) have been studied by using tube — diluation and disc plate technique. The effect of those derivatives upon pathogenic microorganism iso-lated from specimen(urine iwounds,stool, swabs, throat ....etc) have been studied also in comparison with the antibiotics (amikacin,ampicillin, carbencillin, cephalothin, cefoxitin,clindamycin ,erythromycin,gentamycin,penicillin,tetracylin and tri-methoprim. It was shown that derivative(1) had more effective against micro organ-ism than derivative(11).